Waste Generation and Management Practices in Urban Agriculturally Oriented Business for Sustainable Development in South-East, Nigeria - F. M. , Onu; O.A., Obi (Journal of Home Economics Research, 2024)
The study identified urban agricultural waste management as a means for sustainable development in South-eastern Nigeria. Three research questions were posed and answered by the study, while two null hypotheses were formulated and tested at 0.05 level of significance. A multi-stage sampling procedure involving simple random sampling and purposive sampling techniques were used to select 240 registered farmers and 50 Staff of Waste Management Board from a population of 749,538 registered farmers and 1,105 Staff of Waste Management Board in the study area. The total sample of the study was 290. Questionnaire, Focus Group Discussion (FGD) guide and documentary evidence were the instruments used for data collection. Cronbach alpha formula was used to determine the internal consistency of the instrument which gave a reliability coefficient of 0.85. Mean and standard deviation were used to answer the research questions while t-test was used for testing the null hypotheses at 0.05 level of significance. The findings of the study revealed that urban agricultural wastes can be generated through various agricultural operations within the premises used for agriculture or a farm and managed by minimizing activities that generate wastes, reuse and recycle wastes among others. Based on the findings of the study, some recommendations were made.